2019
DOI: 10.1212/wnl.0000000000008544
|View full text |Cite
|
Sign up to set email alerts
|

How common are single gene mutations as a cause for lacunar stroke?

Abstract: ObjectivesTo determine the frequency of rare and pertinent disease-causing variants in small vessel disease (SVD)-associated genes (such as NOTCH3, HTRA1, COL4A1, COL4A2, FOXC1, TREX1, and GLA) in cerebral SVD, we performed targeted gene sequencing in 950 patients with younger-onset apparently sporadic SVD stroke using a targeted sequencing panel.MethodsWe designed a high-throughput sequencing panel to identify variants in 15 genes (7 known SVD genes, 8 SVD-related disorder genes). The panel was used to screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 51 publications
1
44
0
1
Order By: Relevance
“…Hara et al have indicated that HtrA1 is the causative gene of Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL), a genetic cause of stroke in the young 21 . Recently, two rare monogenic variants were identified by target gene sequencing for younger onset lacunar stroke 23 . Patients with CARASIL are characterized by ischemic, non-hypertensive with associated alopecia and spondylosis 24 - 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Hara et al have indicated that HtrA1 is the causative gene of Cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL), a genetic cause of stroke in the young 21 . Recently, two rare monogenic variants were identified by target gene sequencing for younger onset lacunar stroke 23 . Patients with CARASIL are characterized by ischemic, non-hypertensive with associated alopecia and spondylosis 24 - 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported that the NOTCH3 p.R544C mutation was present in a significant number of individuals in Taiwan, including 60 of 7,038 healthy controls (0.9%), 17 of 800 patients with ischemic stroke (2.1%), and 16 of 245 patients with small vessel occlusion stroke (6.5%) from the Taiwan Biobank and that the other two cysteine-altering mutations (p.C853Y, and p.C884Y) were rarely detected (Lee et al, 2020). Furthermore, from the UK DNA Lacunar Stoke Study, Tan et al identified single gene mutations in 14 patients (eight cysteine-altering NOTCH3 variants in 11 patients, two HTRA1 variants in two patients, and one missense COL4A1 variant in one patient) among 950 patients with younger-onset apparently sporadic small vessel disease stroke using a targeted sequencing panel (14 of 950; 1.5%; Tan et al, 2019). These results strongly support our findings, which indicate that NOTCH3 gene mutations may be involved in some cases of lacunar infarction, which is a representative small vessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study is based on a relatively small number of patient because the genetic examination of all 1,094 patients was impractical in terms of cost and time. Patients aged 60-70 years and/or with white matter disease could be good targets for genetic testing (Tan et al, 2019;Lee et al, 2020). Age (60 years or younger), hypertension, and white matter lesions were used as criteria for patient selection in this study but these cohort selection criteria could be seen as arbitrary.…”
Section: Discussionmentioning
confidence: 99%
“…In two patients with VCI-SVD, we identified one patient with a heterozygous pathogenic missense p.P285L variant (NM_002775: c.854C>A) as well as one patient with a heterozygous pathogenic nonsense p.R302 * variant (NM_002775.5: c.904C>T) in the HtrA serine peptidase 1 gene (HTRA1). Both variants is located in the serine protease domain and had been previously reported to be associated with HTRA1-cerebral small vessel disease /CADASIL2 (18)(19)(20)(21).…”
Section: Genetic Variantsmentioning
confidence: 99%